Internationalization strategy of Quinta dos Termos to Germany - Sousa, Francisco Quintas e (2017)
The work project, Internationalization Strategy of Quinta dos Termos to Germany, is about a Portuguese wine company that faces the need to expand to new markets. Thus, this project focuses on exploring the sustainable competitive advantages of the firm, selecting the most suitable target market, assessing that market and defining the best way to enter it. Moreover, an implementation plan is proposed complemented with a financial analysis. This project aims to grant a successful internationalization strategy to Germany and to serve as a guideline to further internationalization projects of Quinta dos Termos.